2020
DOI: 10.1038/s41598-020-71153-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of lncRNA CHRF in cisplatin resistance of ovarian cancer is mediated by miR-10b induced EMT and STAT3 signaling

Abstract: Ovarian Cancer (OC) is a highly lethal gynecological cancer which often progresses through acquired resistance against the administered therapy. Cisplatin is a common therapeutic for the treatment of OC patients and therefore it is critical to understand the mechanisms of resistance against this drug. We studied a paired cell line consisting of parental and cisplatin resistant (CR) derivative ES2 OC cells, and found a number of dysregulated lncRNAs, with CHRF being the most significantly upregulated lncRNA in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…HOXD-AS1 (Chi et al, 2018), PANDAR (Wang et al, 2018), CASC11 (Shen et al, 2019), LINC00152 (Zou and Li, 2019), NCK1-AS1 (Chang et al, 2020), LINC01125 (Guo and Pan, 2019), CCAT1 (Wang D.Y. et al, 2020), NEAT1 (Zhu et al, 2020), CHRF (Tan et al, 2020), ZEB1-AS1 (Dai et al, 2021), TRPM2-AS (Ding et al, 2021), and LOC102724169 (Zhou et al, 2021). While these studies are a testimony to the potential of lncRNAs as modulators of cisplatin resistance, the work has not yet resulted in any clinically relevant therapies.…”
Section: Discussionmentioning
confidence: 98%
“…HOXD-AS1 (Chi et al, 2018), PANDAR (Wang et al, 2018), CASC11 (Shen et al, 2019), LINC00152 (Zou and Li, 2019), NCK1-AS1 (Chang et al, 2020), LINC01125 (Guo and Pan, 2019), CCAT1 (Wang D.Y. et al, 2020), NEAT1 (Zhu et al, 2020), CHRF (Tan et al, 2020), ZEB1-AS1 (Dai et al, 2021), TRPM2-AS (Ding et al, 2021), and LOC102724169 (Zhou et al, 2021). While these studies are a testimony to the potential of lncRNAs as modulators of cisplatin resistance, the work has not yet resulted in any clinically relevant therapies.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, PTEN siRNA could eliminate the distinct proliferation capacity or metastasis ability between miR-4461 overexpression OC cells and control cells. Acquired cisplatin resistance is a serious problem for the therapy of OC patients (8,24). miRNAs actually participated in the regulation of tumorigenesis and drug resistance in OC (11,25).…”
Section: Discussionmentioning
confidence: 99%
“…Acquired cisplatin resistance is a serious problem for the therapy of OC patients ( 8 , 24 ). miRNAs actually participated in the regulation of tumorigenesis and drug resistance in OC ( 11 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al indicated that colon cancer-associated transcript 1 (CCAT1) acted as a miRNA sponge for miR-454 to regulate Survivin expression, thereby enhancing the cisplatin resistance of OC cells [ 10 ]. Besides, downregulation of CHRF reversed the activation of epithelial-to-mesenchymal-transition (EMT) and STAT3 signaling and then improved the sensitivity of OC cells to cisplatin [ 11 ]. lncRNA highly upregulated in liver cancer (HULC), located in chromosome 6p24.3, was reported to be aberrantly elevated in several tumors, including human pancreatic cancer [ 12 ], gastric cancer [ 13 ], osteosarcoma [ 14 ], and OC [ 15 ].…”
Section: Introductionmentioning
confidence: 99%